Contrasting effects of citalopram and reboxetine on waking salivary cortisol. - Harmer, C; Bhagwagar, Z; Shelley, N; Cowen, P (2003)
RATIONALE: Acute administration of antidepressants which potentiate serotonin (5-HT) and noradrenaline (NA) function stimulates the hypothalamic-pituitary-adrenal (HPA) axis and increases salivary free cortisol in healthy subjects. The effects of repeated antidepressant administration have been less studied, but the ability of such treatment to modulate HPA axis activity may be relevant to therapeutic effects. OBJECTIVE: The objective of the study was to assess the effect of short-term treatment with two different antidepressant medications on HPA axis activity. METHODS: We studied the effect of 6-day treatment with the selective serotonin re-uptake inhibitor (SSRI) citalopram (20 mg daily) and the selective noradrenaline re-uptake inhibitor, reboxetine (8 mg daily), on diurnal salivary cortisol in a parallel group, placebo-controlled, double-blind design. RESULTS: Citalopram significantly enhanced the increase in salivary cortisol produced by waking, while the effect of reboxetine treatment was indistinguishable from placebo. There was no change in basal salivary cortisol levels sampled in a standard pattern throughout the day. CONCLUSIONS: Short-term treatment with citalopram and reboxetine produced strikingly different effects on waking salivary cortisol, arguing against a common effect of antidepressant drugs on HPA axis function. Waking salivary cortisol may be a more reliable means of assessing the effects of antidepressant treatment on the HPA axis than a standard regime of basal salivary sampling.